Педагогическая технология актуализации творческого потенциала личности в образовательном процессе - Уварина, Н.В. (My University, 2013)
The article presents developed by the author of pedagogical technology of actualization of the creative potential of personality in the educational process. Pedagogical technology binds together the design, content, procedure and productive side of pedagogical activity; the invariant part of the technology is represented by a sequence of actions: a) definition of pedagogical tasks, b) the choice of method, C) provision of conditions, d) evaluation and correction of results.